Banana nectar as a medium for testing pollen viability and germination in Musa - Nyine, M.; Pillay, M. (2007)
A quick and reliable method for evaluating pollen quality is essential in a breeding program, especially in a crop such as banana that is characterized by high male and female sterility. In this study the germination and viability of banana pollen was evaluated in a sucrose solution and diluted banana nectar. Twenty banana accessions were used to evaluate pollen germination in the two media after 3 and 24 h. Nineteen genotypes (95%) showed significantly higher pollen germination potential (PGP) in diluted nectar than in 3% sucrose solution. The accession TMB2x 8075 - 7 showed no significant pollen germination in nectar and sucrose. Eleven genotypes (55%) showed significant increase in pollen germination by increasing the time of incubation whereas pollen germination for nine genotypes (45%) was not affected by increase in incubation time. Nectar from different banana clones influenced pollen germination suggesting a genotype effect for pollen germination in Musa.